Integrated thermal insulation composite layer and preparation method thereof
By adopting the integrated thermal insulation composite layer in the missile thermal protection structure, the combination of multi -layer materials is used to solve the problem of poor insulation and stability of the traditional thermal protection structure, and realize the efficient insulation of missiles in high temperature environments Fire fire effect.
Patent Information
- Application Number
- CN202411158584.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-08-22
AI Technical Summary
Traditional missile thermal protection structures such as fiber felt and spray coatings have problems such as poor thermal insulation performance, poor stability and large ablation reduction, which is difficult to meet the long-term stable thermal insulation needs of missiles in high temperature environments.
The preparation method of integrated thermal insulation composite layer includes anti -meta -layers, transition layers, heat surface protective layers, heat insulation layers, heat resistance layers and cold surface protective layers. The combination of glue felt and phase -changing materials forms an efficient heating fire protection structure.
The effect of excellent insulation and fire prevention performance, light weight, thin thickness, and good long -term stability is suitable for fire and heat insulation at a high temperature environment of 400 to 1200 ° C.
Smart Images

Figure CN118752879B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fireproof and heat-insulating materials, and in particular to an integrated heat-insulating composite layer and a preparation method thereof. Background Art
[0002] The aerodynamic heat generated during the high-speed flight of the missile will reduce the stiffness and strength of the warhead compartment, and produce thermal stress, thermal strain and other phenomena, while causing the temperature inside the compartment to rise, affecting the stability of the charge. Therefore, during the research and development design process, a thermal insulation protection structure is usually set on its surface. First, it serves the purpose of thermal protection during flight and ensures its performance. Second, it prevents the warhead from being affected by accidental fire and high temperature environment during storage and transportation, thereby ensuring the safety of storage and transportation. However, traditional thermal protection structures mainly include fiber felt, protective coatings, etc. The fiber felt is mainly applied to the surface of the missile that needs thermal protection in the form of a coating. Under long-term high temperature, it (i.e., the fiber felt) has problems such as poor thermal insulation performance, poor stability, and large ablation regression. In order to ensure the thermal insulation performance of the fiber felt, a thicker protective layer is required, which conflicts with the requirement of lightweight thermal insulation of the missile. The protective coating is mainly applied to the surface of the missile that needs thermal protection by spraying. The existing spray coating has problems such as smoking, slagging, cracking, and low bonding strength. During use, it is very easy to fail, which in turn causes the outer surface of the missile to be directly eroded by the high-temperature environment, resulting in poor thermal protection effect and poor stability for long-term use. Summary of the invention
[0003] In view of the problems existing in the above prior art, the object of the present invention is to provide an integrated thermal insulation composite layer and a preparation method thereof. The composite layer prepared by this method has the advantages of good thermal insulation and fireproof performance, light weight, thin thickness, good long-term stability, easy installation, etc., and is thus effectively suitable for thermal protection of the outer surface of a missile.
[0004] The purpose of the present invention is achieved through the following technical solutions:
[0005] A method for preparing an integrated thermal insulation composite layer, the thermal insulation composite layer sequentially comprising an anti-ablation layer, a transition layer, a hot surface protection layer, a thermal insulation layer, a heat-resistant layer and a cold surface protection layer; wherein the anti-ablation layer adopts an intumescent fire retardant coating, the transition layer adopts a primer, the hot surface protection layer and the cold surface protection layer adopt metal titanium foil, the thermal insulation layer adopts an aerogel felt, and the heat-resistant layer adopts a phase change material;
[0006] The specific preparation method is:
[0007] Step 1: Prepare the coatings of the anti-ablation layer and the transition layer as well as the blanks of the hot surface protection layer, the heat insulation layer, the heat resistance layer and the cold surface protection layer as needed, and cut the blanks;
[0008] Step 2: Place the hot surface protection layer on the workbench plane, and attach the heat insulation layer and the heat resistance layer to the end surface of the hot surface protection layer in sequence; then, embed the weldment consisting of the hot surface protection layer, the heat insulation layer and the heat resistance layer into the cold surface protection layer, and then fold the outer circle of the hot surface protection layer inward to form a coating for the cold surface protection layer, and weld their connection (i.e., between the hot surface protection layer and the cold surface protection layer);
[0009] Step 3: First, apply a transition layer on the surface of the hot surface protection layer (i.e., the side away from the thermal insulation layer); then, apply an anti-ablation layer on the surface of the transition layer using a multiple-coating process to obtain a thermal insulation composite layer.
[0010] Based on further optimization of the above scheme, the thickness of the anti-ablation layer is 0.6-1.0 mm; the intumescent fire retardant coating includes a film former, a flame retardant and a functional filler, and the mass ratio between the film former, the flame retardant and the functional filler is 2-3:6-10:1-3; wherein the film former is a high-elasticity polyurethane polymer (wherein the high-elasticity polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 5-8:4-7:2-4; the functional filler is composed of nano-grade aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres, and the mass ratio between them is 5-10:2-5:3-8.
[0011] Based on further optimization of the above scheme, the particle size of the ultrafine ceramic hollow microspheres is 20-50 μm, and the melting point is not less than 1600° C.
[0012] The flame retardant composed of ammonium polyphosphate, pentaerythritol and melamine is combined with a film-forming material to expand and carbonize in a high-temperature environment to form a dense carbonized layer, thereby achieving the purpose of heat insulation and fire prevention; at the same time, functional fillers composed of nano-aluminum hydroxide, expanded graphite and ultra-fine ceramic hollow microspheres are used to, firstly, use nano-aluminum hydroxide to inhibit the amount of smoke and reduce material loss during the high-temperature carbonization process, secondly, enhance the strength of the carbonized layer through nano-aluminum hydroxide, and thirdly, fill the gaps in the expanded carbonized layer through expanded graphite and ultra-fine ceramic hollow microspheres, thereby enhancing the heat insulation performance of the carbonized layer.
[0013] Based on further optimization of the above solution, the thickness of the transition layer is 40 to 60 μm, and the transition layer adopts epoxy primer; the bonding strength between the anti-ablation layer and the hot surface protection layer is improved by the transition layer.
[0014] Based on the further optimization of the above scheme, the thickness of the hot surface protection layer (when the hot surface protection layer is flat) is 0.03-0.1 mm; the hot surface protection layer adopts a metal embossed titanium foil structure, that is, protrusions distributed in an array are arranged on the surface of the flat titanium foil structure; the shape of the protrusions is any one of rice grains, pearls, and water droplets; the diameter of the protrusions is 1-2.5 mm, and the height is 0.4-1.0 mm; the distance between two adjacent protrusions is 4-8 mm; the number of protrusions per unit area in the hot surface protection layer is 1.5x10 4 ~6x10 4 indivual.
[0015] By setting the protrusions on the hot surface protection layer, firstly, the stiffness of the hot surface protection layer is improved through the strain hardening effect generated during the pressing process of the protrusions; secondly, the roughness of the transition layer corresponding to the hot surface protection layer is increased through the distribution of the protrusions, and then the interface bonding force between the hot surface protection layer and the anti-ablation layer is increased by using the transition layer; thirdly, by preparing the protrusions and reducing the wrinkles formed during the molding process of the protective layer, the weak points of failure are reduced, the damage of the protective layer is avoided, and the overall liquid penetration resistance of the composite structure is improved; fourthly, the protrusions provide a buffer gap for the anti-ablation layer to ensure that the anti-ablation layer completes expansion and carbonization while avoiding the anti-ablation. The first is to prevent the layer from cracking and peeling due to the impact force generated by expansion; the second is to convert the reflective surface from mirror reflection to dot matrix diffuse reflection through uneven protrusions, thereby expanding the heat reflection area and improving the reflection efficiency; the third is to utilize the continuous uneven protrusions to cooperate with the thermal insulation layer to form a plurality of cavity matrices, thereby changing the interlayer flow field and forming micro air gaps, effectively blocking heat conduction, inhibiting heat convection, and improving the thermal insulation effect; the fourth is to achieve point contact between the hot surface protection layer and the thermal insulation layer, thereby reducing heat conduction between the hot surface protection layer and the thermal insulation layer, so that the heat is effectively dissipated in the cavity matrix, further improving the thermal insulation effect.
[0016] Based on further optimization of the above scheme, the thickness of the thermal insulation layer is 2 to 5 mm, and the thermal insulation layer adopts basalt fiber reinforced silica aerogel felt; wherein, the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.78 to 1, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.017 to 0.020 W / (m•K).
[0017] Using small-diameter basalt fibers as reinforcing fibers for nanoporous silica aerogel can effectively limit the solid heat conduction of the fibers themselves, making the basalt fiber felt itself have a lower thermal conductivity. At the same time, using short-diameter basalt fibers to form a low-density preform can further reduce the density of the fiber-reinforced aerogel composite while ensuring its mechanical properties. The diameter of the fiber preform is close to the wavelength of near-infrared radiation, which can produce a strong diffraction and scattering effect on the near-infrared radiation, thereby further enhancing the high-temperature infrared radiation heat conduction barrier effect. In addition, the addition of basalt fibers can effectively solve the problems of pure aerogel being brittle and easy to break.
[0018] Based on the further optimization of the above scheme, the volume density of the basalt fiber reinforced silica aerogel felt is 150-170 kg / m 3 The bulk density of the preform formed by basalt fiber is 80~90kg / m 3 The density of silica aerogel is 70~80kg / m 3 .
[0019] Based on the further optimization of the above scheme, the thickness of the heat-resistant layer is 2-5 mm; the phase change material is composited by a phase change raw material and a matrix material, the phase change raw material is a microcapsule, the particle size of the microcapsule is 10-100 μm, wherein the encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea (through the combination of urea and a specific formula, the formaldehyde residue is effectively reduced to avoid affecting the coating performance of the encapsulation material), the phase change core of the microcapsule is paraffin; the matrix material is epoxy resin; the phase change temperature of the phase change material is 95-120°C, and the density is 1.0-1.3 g / cm 3 , phase change enthalpy value is 220~260J / g.
[0020] Based on further optimization of the above scheme, the mass ratio between the epoxy resin (matrix material) and the microcapsule (phase change raw material) is 1:1-15; the mass ratio between the encapsulation material of the microcapsule (i.e., melamine formaldehyde resin) and paraffin is 6:1; the mass ratio of melamine and formaldehyde urea in the encapsulation material is 10:20-30:1-5.
[0021] Based on further optimization of the above solution, the thickness of the cold surface protection layer is 0.03-0.1 mm, and the cold surface protection layer is a flat and smooth metal titanium foil, which is convenient for installation of the cold surface protection layer.
[0022] Based on further optimization of the above scheme, the hot surface protection layer and the cold surface protection layer in step 2 are cleaned and dried with ethyl acetate before use.
[0023] Based on further optimization of the above scheme, the welding process requirements in step 2 are: using 1 to 3 rows of welding, with a welding point spacing of 6±2mm and a welding point indentation diameter of 1±0.5mm.
[0024] Based on further optimization of the above scheme, the multiple coating process of the anti-ablation layer is specifically as follows: the thickness of the anti-ablation layer is K, which is divided into N coatings, and the thickness of each coating is K / N. At the same time, after each layer is coated, it is dried and cured as required to ensure that the next layer can only be constructed after the previous layer is completely cured; the multiple coating process can effectively prevent bulging of the anti-ablation layer, thereby avoiding problems such as pores and cracks during the expansion and carbonization process.
[0025] Based on further optimization of the above scheme, during the coating process of the anti-ablation layer and the transition layer, the construction environment temperature is 5-40°C, the component surface temperature is 5-45°C, the air humidity during the coating process is not more than 90%, and the air circulation at the coating site is maintained and the wind speed is not more than 5m / s.
[0026] The following are the effects of the technical solution of the present invention:
[0027] The present application firstly realizes the purpose of fireproofing and heat insulation by carbonizing the coated anti-ablation layer when it is heated, forming a dense carbonized layer. At the same time, the cooperation of the hot surface protection layer, the transition layer and the anti-ablation layer is utilized to effectively improve the bonding strength therebetween and avoid cracking and falling off of the anti-ablation layer during the expansion and carbonization process. Secondly, it reflects and blocks thermal radiation to achieve heat insulation. Afterwards, the prepared thermal insulation layer and the heat-resistant layer are cooperated to achieve heat insulation through the synergistic effect of phase change heat absorption and aerogel felt, further improving the heat insulation effect. The thermal insulation layer and the hot surface protection layer cooperate to form a large number of cavity matrices to suppress heat conduction and dissipate heat in partitions, thereby avoiding the formation of temperature convergence points and improving the efficiency and effect of heat insulation. Finally, by setting up a smooth cold surface protective layer, firstly, it cooperates with the hot surface protective layer to solidly position and protect the heat insulation layer and the heat resistance layer, avoiding problems such as falling off, offset, and cracking between them (i.e., the heat insulation layer and the heat resistance layer), thereby affecting the heat insulation effect; secondly, it ensures the fit between the composite layer and the component, avoiding the appearance of a bonding gap, thereby avoiding problems such as the composite layer falling off or heat accumulation; thirdly, it improves the overall resistance to infiltration and corrosion of the composite layer. The heat insulation composite layer prepared by this application has the advantages of light weight, thin thickness, easy installation, good long-term stability, strong resistance to infiltration or corrosion, and can be applied to fireproof and heat insulation of various equipment components at 400-1200°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the thermal insulation composite layer in an embodiment of the present invention.
[0029] Figure 2Schematic diagram of the structure of the hot surface protection layer of the thermal insulation composite layer in an embodiment of the present invention.
[0030] Among them, 10, anti-ablation layer; 20, transition layer; 30, hot surface protection layer; 40, thermal insulation layer; 50, heat resistance layer; 60, cold surface protection layer. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0032] Embodiment 1:
[0033] A method for preparing an integrated thermal insulation composite layer, see Figure 1 As shown, the heat-insulating composite layer comprises an anti-ablation layer 10, a transition layer 20, a hot surface protection layer 30, a heat-insulating layer 40, a heat-resistant layer 50 and a cold surface protection layer 60 in sequence; wherein the thickness of the anti-ablation layer 10 is 0.6 mm; the anti-ablation layer 10 adopts an intumescent fire-retardant coating, and the intumescent fire-retardant coating comprises a film-forming material, a flame retardant and a functional filler, and the mass ratio of the film-forming material, the flame retardant and the functional filler is 2:6:1; wherein the film-forming material is a high-elastic polyurethane polymer (wherein the high-elastic The polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 5:4:2; the functional filler is composed of nano-aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres (the average particle size of the ultrafine ceramic hollow microspheres is 20μm, and the melting point is not less than 1600℃), and the mass ratio between them is 5:2:3.
[0034] The thickness of the transition layer 20 is 40 μm, and the transition layer 20 adopts epoxy primer.
[0035] The thickness of the hot surface protection layer 30 (when the hot surface protection layer 30 is flat) is 0.03 mm; the hot surface protection layer 30 adopts a metal embossed titanium foil structure, that is, protrusions distributed in an array are arranged on the surface of the flat titanium foil structure (refer to Figure 2 As shown, the protrusions of the heat surface protection layer 30 are oriented toward the transition layer 20); the shape of the protrusions is rice grain-like; the diameter of the protrusions is 1 mm and the height is 0.4 mm; the distance between two adjacent protrusions is 4 mm; the number of protrusions per unit area in the heat surface protection layer 30 is 6x10 4 indivual.
[0036] The thickness of the heat insulation layer 40 is 2 mm, and the heat insulation layer 40 adopts basalt fiber reinforced silica aerogel felt; wherein, the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.78, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.020 W / (m•K); the volume density of the basalt fiber reinforced silica aerogel felt is 159.74 kg / m 3 The bulk density of the preform formed by basalt fiber is 89.74kg / m 3 The density of silica aerogel is 70kg / m 3 .
[0037] The thickness of the heat-resistant layer 50 is 2 mm. The heat-resistant layer 50 adopts phase change material, which is composed of a phase change raw material and a matrix material. The phase change raw material is a microcapsule, and the average particle size of the microcapsule is 30 μm. The encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the mass ratio of melamine, formaldehyde and urea in the encapsulation material is 10:20:1. The phase change core of the microcapsule is paraffin, and the mass ratio between the encapsulation material (i.e., melamine formaldehyde resin) and the paraffin is 6:1. The matrix material is epoxy resin, and the mass ratio between the epoxy resin (matrix material) and the microcapsule (phase change raw material) is 1:2. The phase change temperature of the phase change material is 95°C, and the density is 1.0 g / cm 3 , phase change enthalpy is 220J / g.
[0038] The thickness of the cold surface protection layer 60 is 0.03 mm, and the cold surface protection layer 60 is a flat and smooth metal titanium foil.
[0039] The specific preparation method is:
[0040] Step 1: Prepare the coatings of the anti-ablation layer 10 and the transition layer 20 as needed (i.e., the raw materials of the anti-ablation layer 10 are uniformly mixed according to the above formula to obtain the coating of the anti-ablation layer 10, and the coating of the transition layer 20 can be an existing product in the art) and the blanks of the hot surface protection layer 30, the heat insulation layer 40, the heat barrier layer 50, and the cold surface protection layer 60 (the hot surface protection layer 30 is prepared by embossing the existing flat and smooth titanium foil with the thickness size in accordance with the above size; the heat insulation layer 40 is prepared by the basalt fiber reinforced silica aerogel according to the above ratio of basalt fiber and silica aerogel The preparation method of the silicon aerogel felt can adopt the existing preparation method of the fiber reinforced aerogel felt; the heat-resistant layer 50 is prepared by uniformly mixing the materials in the above-mentioned proportion; the cold surface protection layer 60 can adopt the titanium foil of the existing composite thickness size), and the blanks are cut (that is, the blanks of the hot surface protection layer 30, the thermal insulation layer 40, the thermal insulation layer 50, and the cold surface protection layer 60 are cut according to the size of the thermal insulation coating required for the component and the required thickness of the thermal insulation layer 40 and the thermal insulation layer 50, and the cutting method is conventional in the art and is not specifically limited in this embodiment).
[0041] Step 2: The hot surface protection layer 30 and the cold surface protection layer 60 are cleaned and dried with ethyl acetate before use; the hot surface protection layer 30 is placed on a workbench plane (specifically: the raised side of the hot surface protection layer 30 is placed downward), and the heat insulation layer 40 and the heat resistance layer 50 are sequentially attached to the end surface of the hot surface protection layer 30; then, the weldment consisting of the hot surface protection layer 30, the heat insulation layer 40 and the heat resistance layer 50 is embedded in the cold surface protection layer 60 (if there is too much edge material and it cannot be embedded, the outer edge of the cold surface protection layer 60 can be appropriately trimmed), and then the outer circle of the hot surface protection layer 30 is folded inward to form a weldment for the cold surface protection layer 60. 0 covering (after folding, the folded part can be knocked with a hammer to fit it to ensure the tightness of the fit); finally, check whether the hot surface protection layer 30, the heat insulation layer 40, the heat resistance layer 50, and the cold surface protection layer 60 have problems such as misalignment and abnormal bulging. If there is no abnormality, weld their joints (i.e. between the hot surface protection layer 30 and the cold surface protection layer 60). The welding process requirements are: single-row welding method, welding point spacing 6±2mm, welding point indentation diameter 1±0.5mm; before starting the welding machine each time, it is necessary to select samples with the same structure and thickness for trial welding at 5 points, and formal welding will be carried out after passing the tear test.
[0042] The edges of the hot surface protection layer 30 and the cold surface protection layer 60 after welding are ground and burrs are removed.
[0043] Step 3: First, apply the transition layer 20 on the surface of the hot surface protection layer 30 (i.e., the side away from the insulation layer 40). Then, the anti-ablation layer 10 is applied on the surface of the transition layer 20 by multiple brushing processes. The multiple brushing processes of the anti-ablation layer 10 are as follows: the thickness of the anti-ablation layer 10 is 0.6 mm, and it is applied 6 times, and the thickness of each brushing is 0.1 mm. At the same time, after each layer is applied, it is dried and cured as required to ensure that the next layer can be constructed only after the previous layer is completely cured; wherein, during the application of the anti-ablation layer 10 and the transition layer 20, the construction environment temperature is 15°C, the surface temperature of the component is 20°C, the air humidity during the application process is not more than 90%, and the air circulation at the application site is maintained and the wind speed is not more than 5m / s. Finally, a thermal insulation composite layer is obtained.
[0044] Embodiment 2:
[0045] A method for preparing an integrated thermal insulation composite layer, see Figure 1 As shown, the heat-insulating composite layer comprises an anti-ablation layer 10, a transition layer 20, a hot surface protection layer 30, a heat-insulating layer 40, a heat-resistant layer 50 and a cold surface protection layer 60 in sequence; wherein the thickness of the anti-ablation layer 10 is 0.8 mm; the anti-ablation layer 10 adopts an intumescent fire-retardant coating, and the intumescent fire-retardant coating comprises a film-forming material, a flame retardant and a functional filler, and the mass ratio of the film-forming material, the flame retardant and the functional filler is 2.5:8:2; wherein the film-forming material is a high-elastic polyurethane polymer (wherein, high The elastic polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 6:5:3; the functional filler is composed of nano-aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres (the average particle size of the ultrafine ceramic hollow microspheres is 35μm, and the melting point is not less than 1600℃), and the mass ratio between them is 8:3:5.
[0046] The thickness of the transition layer 20 is 50 μm, and the transition layer 20 adopts epoxy primer.
[0047] The thickness of the hot surface protection layer 30 (when the hot surface protection layer 30 is flat) is 0.06 mm; the hot surface protection layer 30 adopts a metal embossed titanium foil structure, that is, protrusions distributed in an array are arranged on the surface of the flat titanium foil structure (refer to Figure 2 As shown, the protrusions of the heat surface protection layer 30 are oriented toward the transition layer 20); the shape of the protrusions is pearl-shaped; the diameter of the protrusions is 1.5 mm and the height is 0.7 mm; the distance between two adjacent protrusions is 6 mm; the number of protrusions per unit area in the heat surface protection layer 30 is 3.5x10 4 indivual.
[0048] The thickness of the heat insulation layer 40 is 3 mm, and the heat insulation layer 40 is made of basalt fiber reinforced silica aerogel felt; wherein the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.85, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.018 W / (m•K); the volume density of the basalt fiber reinforced silica aerogel felt is 163.24 kg / m 3 The bulk density of the preform formed by basalt fiber is 88.24kg / m 3 The density of silica aerogel is 75kg / m 3 .
[0049] The thickness of the heat-resistant layer 50 is 3 mm. The heat-resistant layer 50 adopts phase change material, which is composed of a phase change raw material and a matrix material. The phase change raw material is a microcapsule, and the average particle size of the microcapsule is 60 μm. The encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the mass ratio of melamine, formaldehyde and urea in the encapsulation material is 10:25:3. The phase change core of the microcapsule is paraffin, and the mass ratio between the encapsulation material (i.e., melamine formaldehyde resin) and the paraffin is 6:1. The matrix material is epoxy resin, and the mass ratio between the epoxy resin (matrix material) and the microcapsule (phase change raw material) is 1:6. The phase change temperature of the phase change material is 110°C, and the density is 1.2 g / cm 3 , phase change enthalpy is 240J / g.
[0050] The thickness of the cold surface protection layer 60 is 0.06 mm, and the cold surface protection layer 60 is a flat and smooth metal titanium foil.
[0051] The specific preparation method is:
[0052] Step 1: Prepare the coatings of the anti-ablation layer 10 and the transition layer 20 as needed (i.e., the raw materials of the anti-ablation layer 10 are uniformly mixed according to the above formula to obtain the coating of the anti-ablation layer 10, and the coating of the transition layer 20 can be an existing product in the art) and the blanks of the hot surface protection layer 30, the heat insulation layer 40, the heat barrier layer 50, and the cold surface protection layer 60 (the hot surface protection layer 30 is prepared by embossing the existing flat and smooth titanium foil with the thickness size in accordance with the above size; the heat insulation layer 40 is prepared by the basalt fiber reinforced silica aerogel according to the above ratio of basalt fiber and silica aerogel The preparation method of the silicon aerogel felt can adopt the existing preparation method of the fiber reinforced aerogel felt; the heat-resistant layer 50 is prepared by uniformly mixing the materials in the above-mentioned proportion; the cold surface protection layer 60 can adopt the titanium foil of the existing composite thickness size), and the blanks are cut (that is, the blanks of the hot surface protection layer 30, the thermal insulation layer 40, the thermal insulation layer 50, and the cold surface protection layer 60 are cut according to the size of the thermal insulation coating required for the component and the required thickness of the thermal insulation layer 40 and the thermal insulation layer 50, and the cutting method is conventional in the art and is not specifically limited in this embodiment).
[0053] Step 2: The hot surface protection layer 30 and the cold surface protection layer 60 are cleaned and dried with ethyl acetate before use; the hot surface protection layer 30 is placed on a workbench plane (specifically: the raised side of the hot surface protection layer 30 is placed downward), and the heat insulation layer 40 and the heat resistance layer 50 are sequentially attached to the end surface of the hot surface protection layer 30; then, the weldment consisting of the hot surface protection layer 30, the heat insulation layer 40 and the heat resistance layer 50 is embedded in the cold surface protection layer 60 (if there is too much edge material and it cannot be embedded, the outer edge of the cold surface protection layer 60 can be appropriately trimmed), and then the outer circle of the hot surface protection layer 30 is folded inward to form a weldment for the cold surface protection layer 60 (After folding, hammer can be used to knock the folded part to ensure tightness of fit); finally, check whether the hot surface protection layer 30, the heat insulation layer 40, the heat resistance layer 50, and the cold surface protection layer 60 are misaligned, abnormally bulged, etc. If there is no abnormality, weld their joints (i.e., between the hot surface protection layer 30 and the cold surface protection layer 60). The welding process requirements are: double-row staggered welding, welding point spacing 6±2mm, welding point indentation diameter 1±0.5mm; before starting the welding machine each time, it is necessary to select 5 points of samples with the same structure and thickness for trial welding, and formal welding will be carried out after passing the tear test.
[0054] The edges of the hot surface protection layer 30 and the cold surface protection layer 60 after welding are ground and burrs are removed.
[0055] Step 3: First, apply the transition layer 20 on the surface of the hot surface protection layer 30 (i.e., the side away from the insulation layer 40). Then, the anti-ablation layer 10 is applied on the surface of the transition layer 20 by multiple brushing processes. The multiple brushing processes of the anti-ablation layer 10 are as follows: the thickness of the anti-ablation layer 10 is 0.8 mm, and it is applied 8 times, and the thickness of each brushing is 0.1 mm. At the same time, after each layer is applied, it is dried and cured as required to ensure that the next layer can be constructed only after the previous layer is completely cured; wherein, during the application of the anti-ablation layer 10 and the transition layer 20, the construction environment temperature is 25°C, the surface temperature of the component is 30°C, the air humidity during the application process is not more than 90%, and the air circulation at the application site is maintained and the wind speed is not more than 5m / s. Finally, a thermal insulation composite layer is obtained.
[0056] Embodiment 3:
[0057] A method for preparing an integrated thermal insulation composite layer, see Figure 1 As shown, the heat-insulating composite layer comprises an anti-ablation layer 10, a transition layer 20, a hot surface protection layer 30, a heat-insulating layer 40, a heat-resistant layer 50 and a cold surface protection layer 60 in sequence; wherein the thickness of the anti-ablation layer 10 is 1.0 mm; the anti-ablation layer 10 adopts an intumescent fire-retardant coating, and the intumescent fire-retardant coating comprises a film-forming material, a flame retardant and a functional filler, and the mass ratio of the film-forming material, the flame retardant and the functional filler is 3:10:3; wherein the film-forming material is a high-elastic polyurethane polymer (wherein the high-elastic The polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 8:7:4; the functional filler is composed of nano-aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres (the average particle size of the ultrafine ceramic hollow microspheres is 50μm, and the melting point is not less than 1600℃), and the mass ratio between them is 10:5:8.
[0058] The thickness of the transition layer 20 is 60 μm, and the transition layer 20 adopts epoxy primer.
[0059] The thickness of the hot surface protection layer 30 (when the hot surface protection layer 30 is flat) is 0.1 mm; the hot surface protection layer 30 adopts a metal embossed titanium foil structure, that is, protrusions distributed in an array are arranged on the surface of the flat titanium foil structure (refer to Figure 2 As shown, the protrusion direction of the hot surface protection layer 30 is toward the transition layer 20); the shape of the protrusion is a water drop shape; the diameter of the protrusion is 2.5mm and the height is 1.0mm; the distance between two adjacent protrusions is 8mm; the number of protrusions per unit area in the hot surface protection layer 30 is 1.5x10 4 indivual.
[0060] The thickness of the heat insulation layer 40 is 5 mm, and the heat insulation layer 40 adopts basalt fiber reinforced silica aerogel felt; wherein, the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:1, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.017 W / (m•K); the volume density of the basalt fiber reinforced silica aerogel felt is 160 kg / m 3 The bulk density of the preform formed by basalt fiber is 80kg / m 3 , the density of silica aerogel is 80kg / m 3 .
[0061] The thickness of the heat-resistant layer 50 is 5 mm. The heat-resistant layer 50 adopts phase change material, which is composited by phase change raw material and matrix material. The phase change raw material is microcapsule, and the average particle size of the microcapsule is 70 μm. The encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the mass ratio of melamine, formaldehyde and urea in the encapsulation material is 10:30:5. The phase change core of the microcapsule is paraffin, and the mass ratio between the encapsulation material (i.e., melamine formaldehyde resin) and the paraffin is 6:1. The matrix material is epoxy resin, and the mass ratio between epoxy resin (matrix material) and microcapsule (phase change raw material) is 1:8. The phase change temperature of the phase change material is 120°C, and the density is 1.3 g / cm 3 , phase change enthalpy is 260J / g.
[0062] The thickness of the cold surface protection layer 60 is 0.1 mm, and the cold surface protection layer 60 is a flat and smooth metal titanium foil.
[0063] The specific preparation method is:
[0064] Step 1: Prepare the coatings of the anti-ablation layer 10 and the transition layer 20 as needed (i.e., the raw materials of the anti-ablation layer 10 are uniformly mixed according to the above formula to obtain the coating of the anti-ablation layer 10, and the coating of the transition layer 20 can be an existing product in the art) and the blanks of the hot surface protection layer 30, the heat insulation layer 40, the heat barrier layer 50, and the cold surface protection layer 60 (the hot surface protection layer 30 is prepared by embossing the existing flat and smooth titanium foil with the thickness size in accordance with the above size; the heat insulation layer 40 is prepared by the basalt fiber reinforced silica aerogel according to the above ratio of basalt fiber and silica aerogel The preparation method of the silicon aerogel felt can adopt the existing preparation method of the fiber reinforced aerogel felt; the heat-resistant layer 50 is prepared by uniformly mixing the materials in the above-mentioned proportion; the cold surface protection layer 60 can adopt the titanium foil of the existing composite thickness size), and the blanks are cut (that is, the blanks of the hot surface protection layer 30, the thermal insulation layer 40, the thermal insulation layer 50, and the cold surface protection layer 60 are cut according to the size of the thermal insulation coating required for the component and the required thickness of the thermal insulation layer 40 and the thermal insulation layer 50, and the cutting method is conventional in the art and is not specifically limited in this embodiment).
[0065] Step 2: The hot surface protection layer 30 and the cold surface protection layer 60 are cleaned and dried with ethyl acetate before use; the hot surface protection layer 30 is placed on a workbench plane (specifically: the raised side of the hot surface protection layer 30 is placed downward), and the heat insulation layer 40 and the heat resistance layer 50 are sequentially attached to the end surface of the hot surface protection layer 30; then, the weldment consisting of the hot surface protection layer 30, the heat insulation layer 40 and the heat resistance layer 50 is embedded in the cold surface protection layer 60 (if there is too much edge material and it cannot be embedded, the outer edge of the cold surface protection layer 60 can be appropriately trimmed), and then the outer circle of the hot surface protection layer 30 is folded inward to form a weldment for the cold surface protection layer 60 (After folding, hammer can be used to knock the folded part to ensure tightness of fit); finally, check whether the hot surface protection layer 30, the heat insulation layer 40, the heat resistance layer 50, and the cold surface protection layer 60 are misaligned, abnormally bulged, etc. If there is no abnormality, weld their joints (i.e., between the hot surface protection layer 30 and the cold surface protection layer 60). The welding process requirements are: 3 rows of staggered welding, welding point spacing 6±2mm, welding point indentation diameter 1±0.5mm; before starting the welding machine each time, it is necessary to select 5 points of samples with the same structure and thickness for trial welding, and formal welding will be carried out after passing the tear test.
[0066] The edges of the hot surface protection layer 30 and the cold surface protection layer 60 after welding are ground and burrs are removed.
[0067] Step 3: First, apply the transition layer 20 on the surface of the hot surface protection layer 30 (i.e., the side away from the insulation layer 40). Then, the anti-ablation layer 10 is applied on the surface of the transition layer 20 by multiple brushing processes. The multiple brushing processes of the anti-ablation layer 10 are as follows: the thickness of the anti-ablation layer 10 is 1.0 mm, and it is applied 5 times, and the thickness of each brushing is 0.2 mm. At the same time, after each layer is applied, it is dried and cured as required to ensure that the next layer can be constructed only after the previous layer is completely cured; wherein, during the application of the anti-ablation layer 10 and the transition layer 20, the construction environment temperature is 35°C, the surface temperature of the component is 40°C, the air humidity during the application process is not more than 90%, and the air circulation at the application site is maintained and the wind speed is not more than 5 m / s. Finally, a thermal insulation composite layer is obtained.
[0068] Comparative Example 1:
[0069] A composite heat-insulating composite layer, which comprises an anti-ablation layer, a transition layer, a hot surface protection layer, a thermal insulation layer, a heat-resistant layer and a cold surface protection layer in sequence; wherein the thickness and material of the anti-ablation layer, the transition layer, the thermal insulation layer, the heat-resistant layer and the cold surface protection layer are consistent with those in Example 2, the hot surface protection layer has a thickness of 0.06 mm, and the hot surface protection layer adopts a flat and smooth metal titanium foil.
[0070] The preparation method of the above-mentioned heat-insulating composite layer is substantially the same as the preparation method in Example 2, except that when obtaining the blank of the hot surface protection layer in step 1, a smooth titanium foil with existing composite thickness requirements is directly used.
[0071] Comparative Example 2:
[0072] A composite heat-insulating composite layer, the heat-insulating composite layer sequentially comprising an anti-ablation layer, a transition layer, a hot surface protection layer, a first thermal resistance layer and a cold surface protection layer; wherein the thickness and material of the ablation layer, the transition layer, the hot surface protection layer and the cold surface protection layer are consistent with those in Example 2; the thickness of the first thermal resistance layer is 6 mm, the first thermal resistance layer adopts basalt fiber reinforced silica aerogel felt, the diameter of the basalt fiber is not more than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.85, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.018 W / (m•K); the volume density of the basalt fiber reinforced silica aerogel felt is 163.24 kg / m 3 The bulk density of the preform formed by basalt fiber is 88.24kg / m 3 The density of silica aerogel is 75kg / m 3 .
[0073] The preparation method of the above-mentioned thermal insulation composite layer is generally consistent with the preparation method in Example 2, except that: in step 1, only the blank of the first thermal resistance layer is blanked, and the blanks of the thermal insulation layer 40 and the thermal resistance layer 50 are not blanked; during the composite in step 2, only the first thermal resistance layer is stacked between the hot surface protection layer and the cold surface protection layer.
[0074] Comparative Example 3:
[0075] A composite heat-insulating composite layer, the heat-insulating composite layer sequentially comprises an anti-ablation layer, a transition layer, a hot surface protection layer, a second thermal resistance layer and a cold surface protection layer; wherein the thickness and material of the ablation layer, the transition layer, the hot surface protection layer and the cold surface protection layer are consistent with those in Example 2; the thickness of the second thermal resistance layer is 6 mm; the second thermal resistance layer adopts a phase change material, the phase change material is composited by a phase change raw material and a matrix material, the phase change raw material is a microcapsule, the average particle size of the microcapsule is 60 μm, wherein the microcapsule The encapsulation material of the capsule is a mixture of melamine, formaldehyde and urea, and the mass ratio of melamine, formaldehyde and urea in the encapsulation material is 10:25:3; the phase change core of the microcapsule is paraffin, and the mass ratio between the encapsulation material (i.e. melamine formaldehyde resin) and the paraffin is 6:1; the matrix material is epoxy resin, and the mass ratio between epoxy resin (matrix material) and microcapsule (phase change raw material) is 1:6; the phase change temperature of the phase change material is 110°C and the density is 1.2g / cm 3 , phase change enthalpy is 240J / g.
[0076] The preparation method of the above-mentioned thermal insulation composite layer is generally consistent with the preparation method in Example 2, except that: in step one, only the blank of the second thermal resistance layer is blanked, and the blanks of the thermal insulation layer 40 and the thermal resistance layer 50 are not blanked; during the composite in step two, only the second thermal resistance layer is stacked between the hot surface protection layer and the cold surface protection layer.
[0077] Comparative Example 4:
[0078] A method for preparing an integrated thermal insulation composite layer, the thermal insulation composite layer sequentially comprising an anti-ablation layer, a transition layer, a hot surface protection layer, a thermal insulation layer, a heat-resistant layer and a cold surface protection layer; wherein the thickness and material of the transition layer, the hot surface protection layer, the thermal insulation layer, the heat-resistant layer and the cold surface protection layer are consistent with those in Example 2; the thickness of the anti-ablation layer is 0.8 mm; an intumescent fire retardant coating is used, the intumescent fire retardant coating comprises a film-forming material, a flame retardant and a functional filler, and the mass ratio of the film-forming material, the flame retardant and the functional filler is 2.5:8:2 ; Among them, the film-forming material is a high-elastic polyurethane polymer (wherein, the high-elastic polyurethane polymer is polymerized by one or two of polycaprolactone diol, polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 6:5:3; the functional filler is composed of expanded graphite and ultrafine ceramic hollow microspheres (the average particle size of the ultrafine ceramic hollow microspheres is 35μm, and the melting point is not less than 1600℃), and the mass ratio between them is 3:5.
[0079] The preparation method of the above-mentioned thermal insulation composite layer is substantially the same as the preparation method in Example 2, except that: in the preparation process of the anti-ablation layer coating in step 1, the functional filler of nano-aluminum hydroxide is not added.
[0080] The thermal insulation composite layer samples in Examples 1 to 3 and Comparative Examples 1 to 4 were fixed on the tooling of the inner cavity of the heating equipment, and three thermocouples were arranged on the cold surface of the sample and evenly distributed on the cold surface of the sample. When the ambient temperature was 25 degrees Celsius (the other test conditions were also the same) and the hot surface temperature was 800°C, the cold surface temperature of the corresponding sample was obtained, and the test time was 300s. The test results are as follows:
[0081]
[0082] As shown in the table above: the use of the structural combination of the specific anti-ablation layer, transition layer, hot surface protection layer, thermal insulation layer, heat-resistant layer, and cold surface protection layer of the present application in combination with the specific material combination of the corresponding structural layer can effectively improve the fireproof and heat-insulating properties of the composite layer. Under the action of the hot surface temperature of 800°C for a long time (i.e., 300s), the average cold surface temperature of the thermal insulation composite layer prepared by the present application is not more than 60°C, which is significantly lower than that of the composite layers prepared in Comparative Examples 1 to 4; at the same time, the temperature difference of each temperature measuring point of the composite layer prepared by the present application is small, which proves that the structure of the present application can dissipate heat evenly and there is no temperature concentration point, while the temperature deviation of the temperature measuring point of the composite layer in Comparative Examples 1 to 4 is large, which also indirectly proves that the interlayer heat insulation effect of the present application is good.
Claims
1. A method for preparing an integrated thermal insulation composite layer, characterized in that: The thermal insulation composite layer comprises an anti-ablation layer, a transition layer, a hot surface protection layer, a thermal insulation layer, a heat-resistant layer and a cold surface protection layer in sequence; wherein the anti-ablation layer adopts an intumescent fire-retardant coating, the transition layer adopts a primer, the hot surface protection layer and the cold surface protection layer adopt metal titanium foil, the thermal insulation layer adopts aerogel felt, and the heat-resistant layer adopts a phase change material; The thickness of the anti-ablation layer is 0.6-1.0 mm. The intumescent fire retardant coating comprises a film former, a flame retardant and a functional filler. The mass ratio of the film former, the flame retardant and the functional filler is 2-3:6-10:1-3. The film former is a high-elastic polyurethane polymer, which is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI. The flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio of them is 5-8:4-7:2-4. The functional filler is composed of nano-scale hydroxide The heat surface protection layer is composed of aluminum, expanded graphite and ultrafine ceramic hollow microspheres, and the mass ratio between them is 5-10:2-5:3-8; the thickness of the hot surface protection layer is 0.03-0.1 mm, and the hot surface protection layer adopts a metal embossed titanium foil structure, that is, protrusions distributed in an array are arranged on the surface of the flat titanium foil structure; the shape of the protrusions is any one of rice grains, pearls, and water drops; the diameter of the protrusions is 1-2.5 mm, and the height is 0.4-1.0 mm; the distance between two adjacent protrusions is 4-8 mm; the number of protrusions per unit area in the hot surface protection layer is 1.5x10 4 ~6x10 4 The thickness of the cold surface protection layer is 0.03-0.1 mm, and the cold surface protection layer is a flat and smooth metal titanium foil; The specific preparation method is: Step 1: Prepare the coatings of the anti-ablation layer and the transition layer as well as the blanks of the hot surface protection layer, the heat insulation layer, the heat resistance layer and the cold surface protection layer as needed, and cut the blanks; Step 2: Place the hot surface protection layer on the workbench plane, and attach the heat insulation layer and the heat resistance layer to the end surface of the hot surface protection layer in sequence; then, embed the weldment consisting of the hot surface protection layer, the heat insulation layer and the heat resistance layer into the cold surface protection layer, and then fold the outer circle of the hot surface protection layer inward to form a coating for the cold surface protection layer, and weld their joints; Step 3: First, a transition layer is applied on the surface of the hot surface protection layer; then, an anti-ablation layer is applied on the surface of the transition layer using a multiple-coating process to obtain a heat-insulating composite layer.
2. The method for preparing an integrated thermal insulation composite layer according to claim 1, characterized in that: The thickness of the transition layer is 40-60 μm, and the transition layer adopts epoxy primer.
3. The method for preparing an integrated thermal insulation composite layer according to claim 1 or 2, characterized in that: The thickness of the thermal insulation layer is 2 to 5 mm, and the thermal insulation layer is made of basalt fiber reinforced silica aerogel felt; wherein the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.78 to 1, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.017 to 0.020 W / (m•K).
4. The method for preparing an integrated thermal insulation composite layer according to claim 1 or 2, characterized in that: The thickness of the heat-resistant layer is 2 to 5 mm; the phase change material is composited by a phase change raw material and a matrix material, the phase change raw material is a microcapsule, the particle size of the microcapsule is 10 to 100 μm, wherein the encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the phase change core of the microcapsule is paraffin; the matrix material is epoxy resin; the phase change temperature of the phase change material is 95 to 120°C, and the density is 1.0 to 1.3 g / cm 3 , phase change enthalpy value is 220~260J / g.
5. The method for preparing an integrated thermal insulation composite layer according to claim 1, characterized in that: In the step 2, the hot surface protective layer and the cold surface protective layer are cleaned and dried with ethyl acetate before use.
6. The method for preparing an integrated thermal insulation composite layer according to claim 1, characterized in that: The welding process requirements in step 2 are: using 1 to 3 rows of welding, with a welding point spacing of 6±2mm and a welding point indentation diameter of 1±0.5mm.
7. The method for preparing an integrated thermal insulation composite layer according to claim 1, characterized in that: The multiple coating process of the anti-ablation layer is specifically as follows: the thickness of the anti-ablation layer is K, and it is coated N times, and the thickness of each coating is K / N. At the same time, after each layer is coated, it is dried and cured as required to ensure that the next layer can be constructed only after the previous layer is completely cured.
Citation Information
Patent Citations
Fireproof composite carriage
CN210190788U